A content analysis of Visiting Friends and Relatives (VFR) travel research. (December 2015) - Yousuf, Mohammad; Backer, Elisa
Abstract: Visiting Friends and Relatives (VFR) travel is a significant form of tourism worldwide. Scholarly research into VFR commenced in 1990 and since then only one review of the literature has been conducted, which was a content analysis based exclusively on journal articles. That research, based from 1990 to 2010 highlighted that only 39 VFR articles had been published in tourism journals. Given the small number of publications identified, it was felt that an analysis encompassing a wider selection of publication forums and extended to 2015 would be valuable to scholarship. This research also considered citations and outputs by individual authors to determine where research is being derived from. The findings of this research identified recent growth in VFR travel research from wider publication forums, including conference papers and theses. However, VFR has made the most presence through book chapters in recent years. VFR research has historically focused on the commercial and marketing aspects, but more recently has turned to furthering understanding of the social aspects by giving particular importance to the VFR hosts and migration topics for the future direction of VFR research.